Female Victims of Domestic Violence from an Islamic Perspective (A Study on Women experiencing Domestic Violence at the Nurul Islam Orphanage, Serang) - Meilla Dwi Nurmala; Septi Kuntari; Evi Afiati (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2022)
This study aimed to depict the life of female victims of domestic violence. To this end, a qualitative case study was conducted. Data were collected through interviews (curriculum vitae), observation, document interpretation, and survey (result) and analyzed using triangulation. The finding pictured several acts of domestic violence against children committed by their parents. The finding could serve as a reference for counselors to help solve problems with appropriate techniques according to the problem.